The praxis of project-based learning at PIKA Vocational Secondary School Semarang - Wahyu Noviansyah; Putu Sudira (Jurnal Pendidikan Vokasi, 2020)
This study aims to find out the praxis of project-based learning at PIKA Vocational Secondary School Semarang and to identify the advantages and disadvantages. The design of this research is a qualitative case study. The data collection techniques were in-depth interviews, participant observation, and document analysis. The informants of this study were: principal, vice-principal, teachers, employees, and students. This study shows that: (1) there are two patterns of project-based learning at PIKA VSS Semarang. The first pattern is an internal internship program, and the second is learning a productive practice program. (2) The advantages of project-based learning are: (a) it trains the students' sense of entrepreneurship; (b) it develops learning motivation; (c) it gives a complete, real and contextual learning experience; and (d) it develops the students' hard skills and soft skills. The disadvantages of project-based learning are: (a) it requires the acquisition competencies to perform project assignments; (b) it takes times; (c) it requires high operational costs; (d) it requires adequate facilities.